Implementation Strategy of Digital Visualization-Based Management System in Baitul Arqom Non-Formal Islamic Education - Endy Sjaiful Alim; Fadhli Asril; Ahmad Subagyo (Journal of Educational Management Research, 2026)
This study aims to formulate a comprehensive implementation strategy for a digital visualization-based management system in the Baitul Arqom program as a core non-formal Islamic education initiative for cadre regeneration to improve data utilization and decision-making efficiency. This research employs a qualitative descriptive approach, with data collected through in-depth interviews with administrators of the Council for Cadre Education (Majelis Pendidikan Kader) and Focus Group Discussions (FGD), which were analyzed using SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). The findings indicate that although Baitul Arqom has a strong organizational structure and ideological foundation, its management remains constrained by manual administrative processes, limited technological infrastructure, and low digital literacy among senior administrators. Based on the SWOT analysis, a three-phase implementation strategy was formulated, consisting of infrastructure modernization, human resource capacity building, and the development of a digital visualization dashboard for real-time monitoring and evaluation. This study implies that the successful implementation of a visualization-based management system requires a holistic approach that prioritizes organizational culture transformation, continuous capacity development, and phased system adoption to ensure sustainable and data-driven cadre management within the Baitul Arqom program